DEMYSTIFYING HEALTHCARE CLAIMS ADJUDICATION: HOW AUTOMATION REDUCES ERRORS AND SPEEDS UP PAYMENTS - PEEYUSH KHANDELWAL (IPHO-Journal of Advance Research in Science And Engineering, 2026)
Healthcare claims adjudication can refer to the set of operations that make up the lifecycle of an insurance reimbursement claim: eligibility verification, benefits and pricing determination, and patient liability determination. Manual processes used by payers to support this lifecycle are generally inefficient and result in increased operational error, variable coverage decisions, and long payment turnarounds, all of which may harm payers, patients, and providers. Automation technologies, like rule-based processing engines, real-time eligibility checks, and predictive analytics, help make the claims process more efficient by using consistent rules, spotting mistakes as they happen, and speeding up payment. Interoperability technologies, using APIs, make sure that adjudication systems regularly check and update claims with enrollment files, provider directories, and Advanced anomaly detection features. These can improve just-in-time claims processing by not only checking claims against rules but also spotting fraud and cleaning up claims before they are submitted, helping to catch den By automating the claims process for everyone involved—providers, patients, and payers—those managing the revenue cycle can look forward to getting paid faster, having fewer claims denied, providing clearer financial information to patients, and reducing the costs of handling each claim, which makes smart adjudication systems essential for efficient revenue cycles in today’s healthcare.